Doa Syafaat Yesus dalam Yohanes 17: Fondasi Teologi Persatuan Gereja - Elvin Paende; Sherly Mudak (STT Saint Paul Bandung, 2026)
Church unity is a central theme in New Testament theology, but it is often narrowed down to issues of organization or denominational uniformity. John 17 offers a different perspective through Jesus' intercessory prayer, which places unity at the heart of God's mission for the world. This study aims to explore the theological meaning of Jesus’ intercessory prayer, focusing on church unity as a declaration of mission rooted in the Trinitarian relationship of love. A research gap is identified in the tendency of previous literature to separate discussions of unity from the ontological and missiological dimensions of this prayer. The novelty of this article lies in interpreting unity not merely as Jesus’ petition but as a declaration of the church’s mission rooted in perichoresis; the participation of the faithful in the unity of the Father and the Son’s love. Using qualitative methods and a literature review approach, this study examines the structure of the prayer (John 17:1–26), the meaning of “being one” in the Trinitarian relationship, and the theological and practical implications for the church today. The results of the study show that: (1) unity is the climax of Jesus' intercessory prayer, (2) unity reflects the love and glory of the Trinity, (3) unity functions as a mission statement to convince the world of Christ's commission, and (4) True unity requires a shift from structural unity to relational unity that is alive with God's love. This article asserts that church unity is not merely social ethics, but a divine reality that serves as a means of God's revelation to the world.